Antimicrobial use quantification in adult dairy cows – Part 1 – Standardized regimens as a method for describing antimicrobial use. Issue 1 (17th November 2020) - Schrag, Nora F. D.; Apley, Michael D.; Godden, Sandra M.; Lubbers, Brian V.; Singer, Randall S.
Abstract: This study describes a process to acquire and convert farm treatment records into a standardized regimen format. Multiple sources of on‐farm data were utilized to convert the original treatment records to standardized regimens, enabling the generation of objective, granular descriptions of antimicrobial use. These standard regimen descriptions allow antimicrobial use data to be qualitatively stratified by active substance, disease syndrome treated, use category, and route of administration. Quantitative distributions are available for the grams of active substance per administration, the grams of active substance per regimen, the number of administrations, number of days of therapy and the time frame between the first and last administration. Granular quantification by this method informs future research, surveillance and policy.